Crystal violet staining is a reliable alternative to bicinchoninic acid assay-based normalization - Nilles, Julie; Weiß, Johanna; Theile, Dirk (BioTechniques, 2022)
Experimental data with cells often require normalization. The frequently used bicinchoninic acid (BCA) assay, in fact, indicates protein content but is influenced by incubation time, pH etc. A simple, rapid and reliable alternative is desirable. Crystal violet stains nucleic acids and proteins and was used to reflect the cell number in 96-well plates. Calibration curves and comparison with BCA confirmed excellent goodness of fit (R2: 0.98), conformity (nonsignificant difference of BCA to crystal violet) and reliability of this staining methodology. Crystal violet staining can be used to normalize experimental data to the number of adherent cells present in cell culture plates.